1 - Conscientious Achievements of the Dangme before the Atlantic Contact: Insights from Archaeological and Ethnohistorical Investigations at Sega and Kpone, Greater Accra Region, Ghana - Fritz Biveridge (Afrika Zamani, 2022)
This article summarizes results of archaeological research conducted at Sega and Kpone, two ancient Dangme settlements located along the Gulf of Guinea in Ghana. Ethno-historical narratives and written records constituted other data sources used. The objective of the study was to utilize data from the above sources to deepen and enhance our understanding of ancient cultural life-ways of the settlers of the two sites before their encounter with Europeans. The combined evidence indicated that the settlement population was relatively large and sophisticated, attested by the extensive occupational areas and the existence of several specialist vocations. Another significant development was that the indigenous populations were engaged in complex intra-regional exchanges with neighbouring polities which impacted positively on the local economy and appears to have facilitated urbanization and state formation processes.